Menumbuhkan Sikap Sadar Lingkungan Bagi Anak Usia Sekolah Dasar - Laelia Nurpratiwiningsih; Teguh Arifianto; Wildan Qosid; Ubaedillah Ubaedillah (JAMU : Jurnal Abdi Masyarakat UMUS, 2020)
The environment is very important to society, because it is interconnected between living creatures and surrounding areas. The implementation of a clean and healthy environment needs to be implemented early. In its application environmental awareness can be applied in elementary school. Elementary school age children need to be aware of wasting garbage in their place. The types of garbage that exist in the community environment are very variant, so it is necessary to be known and chosen by the child in throwing. The method of implementation of make a match method using image media and question and answer. Results showed that elementary school-age children were enthusiastic in cultivating environmental awareness and simply having an understanding of the environmental conscious attitude. In addition, the child has an understanding related to the types of garbage in the surrounding environment.